Rede social e capital social em um clube de serviço: o caso do Rotary Club São Paulo Avenida Paulista - Ferreira, Helen de Montille (2010)
A service club is a voluntary association of individuals, professionals with a common goal. It is an area of civic and political socialization where its members implement citizenship. Rotary International is one of the largest service club in the world with 105 years of existence. It has been conducted a quantitative and qualitative research to verify the characteristics of a service club of Rotary International, Rotary Club São Paulo Avenida Paulista, which develops social projects in various areas relevant to society. It is presented the socio-economic relations of the associates and relationships that they lay in the formulation and implementation of social projects. The analysis of network and social capital is the pillar of support of the members for the existence of social relevance. It discusses the importance of partnerships in the implementation of projects. The donation system, that permeates the club, brings an understanding for the commitment of the volunteers involved. Through network analysis it has been verified the internal and external relationships of the club, as well as the movement of capital by reciprocity and the motivations of volunteers. The research has revealed that the associate profile is a well established businessman, interested in using their profession to improve the quality of life of society. The internal network between members, reveals a leadership based on knowledge. The leadership does not follow the hierarchical structure of the club. The national and international network has proved to be small without large amounts of bonds. There are subgroups where the members participate in several at once. Social capital highlights the cooperation and trust between members of the international organization. The associates use the individual networks to implement the projects. There is a retribution of volunteer work performed, proving the theory of giving supports and motivates members